Spiritual Pilgrimage as Metaphor and Movement in Adult Learning: The Transformative Journey Toward Wisdom - Perdeta L. Bush; Elizabeth J. Tisdell (Adult Education Research Conference, 2012)
This paper explores the notion of spiritual pilgrimage in the lives of a multicultural group of adult educators who have been participants in a longitudinal study of their spiritual development, and to some extent how it connects to our own stories as educators and researchers
Keywords: spiritual pilgrimage; transformative journey; wisdom